Tamsulosin Versus Alfuzosin as Medical Expulsion Therapy for Distal Ureteric Calculi: An Analytical Study - Kumar, Vijay; Bhatta, Pashupati; Yadav, Umesh; Singh, Amit; Raya, Akash (Journal of Institute of Medicine Nepal, 2021)
Introduction: Urolithiasis is one of the most common urological problems. About 20% of urolithiasis accounts for ureteric calculi among which 2/3rd patients present with distal ureteric calculi. Alpha blockers are commonly used for effective treatment of ureteric calculi. The aim of this study was to compare effectiveness of Tamsulosin and Alfuzosin as medical expulsion therapy. Methods: This analytical study was carried out at National Medical College Department of Surgery, Urology Unit, Birgunj from October 2020 to March 2021. Ethical clearance (FNMC/439/075/76) was obtained from institutional review committee. Total 100 cases were included in the study who presented with distal ureteric calculi of <10 mm. The patients receiving Tamsulosin were recruited in Group T and those receiving Alfuzosin were recruited into Group A. The choice of treatment was made by the treating surgeons. Tamsulosin 0.4 mg was used for the patients in Group T and 10 mg Alfuzosin was used in Group A. Patients were followed-up weekly for 4 weeks. Stone expulsion rate, time to stone expulsion, colic episodes, emergency visit, use of analgesics and drug-related side-effects were recorded. Results: The rate of expulsion of stone in Tamsulosin group was 64% and that in Alfuzosin group was 66%. The expulsion time in Tamsulosin group was 4.28±3.49 days and that in Alfuzosin group was 5.02±4.09 days which was statistically insignificant (p=0.33). Mean episodes of colic and use of analgesics were similar in both groups. Backache was the most common side effect in both groups. Conclusion: Efficacy of both Alfuzosin 10 mg and Tamsulosin 0.4 mg as medical expulsion therapy is comparable to each other with minimum side effects of both the drugs.